USB LED lighting tube - Hisaji, Noda; Mohd Rashid, Muhammad Ikram; Abdullah, R.; Razali, Saifudin (2019)
This project entails development of a power electronic controller for a LED lighting system as the low consumption lighting system. Many of today’s portable electronics require backlight LED-driver solutions with the following features: direct control of current, high efficiency, PWM dimming, overvoltage protection, load disconnect, small size, and ease of use. This article discusses each of these features and how they are achieved, and conclude with a typical circuit that implements each of these features. Many portable LED applications require dimming. In applications such as LCD backlighting, dimming provides brightness and contrast adjustment. Two types of dimming are available: analog and PWM. With analog dimming, 50% brightness is achieved by applying 50% of the maximum current to the LED. Drawbacks to this method include LED color shift and the need for an analog control signal, which is not usually readily available. PWM dimming is achieved by applying full current to the LED at a reduced duty cycle. For 50% brightness, full current is applied at a 50% duty cycle. The frequency of the PWM signal must be above 100 Hz to ensure that the PWM pulsing is not visible to the human eye. The maximum PWM frequency depends upon the power-supply startup and response times. To provide the most flexibility and ease of integration, the LED driver should be able to accept PWM frequencies as high as 50 kHz.